Perspectives on Policy Formation - Worth, Walter H. (Canadian Journal of Higher Education, 1978)
Most of the rhetoric about the relationship between policy formation and research is rooted in the familiar rational model. But as is so often the case in human affairs, our deeds deny our discourse} At best, the decision process can lay claim to only limited rationality. This paper seeks to offer at least a partial explanation for this phenomenon and to suggest some ways of improving the linkage between research and policy formation. To achieve this two-fold purpose three theories accounting for the non-utilization of research will be noted and followed by a brief description of certain ways in which administrators seem to use research. Then two major situational factors which influence our use pattern will be elaborated. Finally, some implications will be derived for future action within an increasingly political framework. Throughout, the usual litany about the short-comings of educational research will be avoided. The perspective for these observations is that of an administrator. Thus, their source is primarily experience and intuition, buttressed wherever possible by the wisdom to be found in the professional literature.